Enantiomer‐specific pharmacokinetics of D, L‐3‐hydroxybutyrate: Implications for the treatment of multiple acyl‐CoA dehydrogenase deficiency. Issue 4 (15th February 2021) - van Rijt, Willemijn J.; Van Hove, Johan L. K.; Vaz, Frédéric M.; Havinga, Rick; Allersma, Derk P.; Zijp, Tanja R.; Bedoyan, Jirair K.; Heiner‐Fokkema, M. R.; Reijngoud, Dirk‐Jan; Geraghty, Michael T.; Wanders, Ronald J. A.; Oosterveer, Maaike H.; et al.
Abstract: D, L‐3‐hydroxybutyrate (D, L‐3‐HB, a ketone body) treatment has been described in several inborn errors of metabolism, including multiple acyl‐CoA dehydrogenase deficiency (MADD; glutaric aciduria type II). We aimed to improve the understanding of enantiomer‐specific pharmacokinetics of D, L‐3‐HB. Using UPLC‐MS/MS, we analyzed D‐3‐HB and L‐3‐HB concentrations in blood samples from three MADD patients, and blood and tissue samples from healthy rats, upon D, L‐3‐HB salt administration (patients: 736‐1123 mg/kg/day; rats: 1579‐6317 mg/kg/day of salt‐free D, L‐3‐HB). D, L‐3‐HB administration caused substantially higher L‐3‐HB concentrations than D‐3‐HB. In MADD patients, both enantiomers peaked at 30 to 60 minutes, and approached baseline after 3 hours. In rats, D, L‐3‐HB administration significantly increased C max and AUC of D‐3‐HB in a dose‐dependent manner (controls vs ascending dose groups for C max : 0.10 vs 0.30‐0.35‐0.50 mmol/L, and AUC: 14 vs 58‐71‐106 minutes*mmol/L), whereas for L‐3‐HB the increases were significant compared to controls, but not dose proportional ( C max : 0.01 vs 1.88‐1.92‐1.98 mmol/L, and AUC: 1 vs 380‐454‐479 minutes*mmol/L). L‐3‐HB concentrations increased extensively in brain, heart, liver, and muscle, whereas the most profound rise in D‐3‐HB was observed in heart and liver. Our study provides important knowledge on the absorption and distribution upon oral D, L‐3‐HB. The enantiomer‐specific pharmacokinetics implies differential metabolic fates of D‐3‐HB and L‐3‐HB.